Nitrogen Fertility and Cultivar Effects on Potato Agronomic Properties and Acrylamide‐forming Potential. (1st January 2019) - Sun, Na; Wang, Yi; Gupta, Sanjay K.; Rosen, Carl J.
Abstract : Core Ideas: Agronomic practices can affect compounds involved with acrylamide formation in processed potato Increasing N rate increased tuber asparagine Tuber reducing sugars were not consistently affected by N rate Newly developed cultivars had lower acrylamide forming potential than Russet Burbank Acrylamide is a potentially harmful compound when consumed in the human diet and is formed during potato ( Solanum tuberosum L.) processing from the precursors reducing sugars and asparagine. The objective of this study was to determine the effects of N rate (135–404 kg ha −1 ) on tuber yield and quality and tuber reducing sugars and asparagine concentrations in newly released cultivars Easton and Dakota Russet, relative to the standard cultivar Russet Burbank. Tuber samples were collected at intervals from initial set through harvest during two growing seasons. Tuber yield of all cultivars increased quadratically with increasing N rate. Highest yield was produced by Easton, followed by Russet Burbank and Dakota Russet. Russet Burbank had more tubers per plant than the new cultivars. Specific gravity decreased with increasing N rate and was lowest in Russet Burbank both years. The new cultivars had a lower hollow heart incidence than Russet Burbank when environmental conditions were favorable for hollow heart development. Tuber‐reducing sugars changed during the growing season but were related more to cultivar and growing conditions than N rate. New cultivars had lower reducing sugars than Russet Burbank. In contrast to reducing sugars, asparagine increased with increasing N rate and was less affected by environmental conditions during the growing season. Easton had slightly lower asparagine concentrations than Russet Burbank and Dakota Russet. This study indicates that cultivar and growing conditions have a dominant effect on tuber‐reducing sugars, while N rate has a more consistent effect on tuber asparagine.